Effects of feeding processed kidney bean meal (Phaseolus vulgaris) by replacing soybean meal on egg fertility and qualities of chicks of white leghorn hens - Fikru, Sisay; Urge, Mengistu; Animut, Getachew (Journal of Advanced Veterinary and Animal Research, 2015)
A study was conducted to evaluate the effects of feeding processed kidney bean meal (PKBM) by replacing soybean meal (SBM) on fertility, hatchability, embryonic mortality and chick quality of white leghorn (WL) hens. A total of 225 white leghorn hens (195 layers and 30 cocks) with uniform body weight (BW) and age were randomly distributed into 15 pens and assigned to five treatments (i.e., T1, T2, T3, T4, and T5). A total of 360 eggs collected from all the treatment birds were used for the analysis. The feeds of the treatments were SBM substituted by PKBM at 0, 25, 50, 75 and 100% levels for T1, T2, T3, T4, and T5, respectively. Replacement of SBM with PKBM in the diet did not affect the fertility, hatchability, embryonic mortality, chick length, chick weight, and chick quality by visual score. As no difference is observed, 100% replacement of SBM by PKBM (dosed at 100 g/kg concentrate diet) is possible. http://dx.doi.org/10.5455/javar.2015.b66